2020
DOI: 10.1080/14756366.2020.1816999
|View full text |Cite
|
Sign up to set email alerts
|

Rational design of small molecules able to inhibit α-synuclein amyloid aggregation for the treatment of Parkinson’s disease

Abstract: Parkinson’s disease is one of the most common neurodegenerative disorders in elderly age. One of the mechanisms involved in the neurodegeneration appears related to the aggregation of the presynaptic protein alpha synuclein (α-syn) into toxic oligomers and fibrils. To date, no highly effective treatment is currently available; therefore, there is an increasing interest in the search of new therapeutic tools. The modulation of α-syn aggregation represents an emergent and promising disease-modifying strategy for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 30 publications
2
16
0
Order By: Relevance
“…As shown in Figure 7B, ISO mainly interacted with the NAC region of α-synuclein through forming two hydrogen bonds with Glu61 and Gly73. Our result was in well consistent with that of Vittorio et al, who identified that amyloid fibril inhibitors targeting to α-synuclein bind in the sites located between the N-terminal and the NAC domains of the protein [14]. Therefore, we assume that αsynuclein is the putative target of ISO that can be directly bound by ISO in PD.…”
Section: Interaction Between Iso and α-Synucleinsupporting
confidence: 93%
See 2 more Smart Citations
“…As shown in Figure 7B, ISO mainly interacted with the NAC region of α-synuclein through forming two hydrogen bonds with Glu61 and Gly73. Our result was in well consistent with that of Vittorio et al, who identified that amyloid fibril inhibitors targeting to α-synuclein bind in the sites located between the N-terminal and the NAC domains of the protein [14]. Therefore, we assume that αsynuclein is the putative target of ISO that can be directly bound by ISO in PD.…”
Section: Interaction Between Iso and α-Synucleinsupporting
confidence: 93%
“…The chemical structure of ISO (CID: 5281255) was prepared from PubChem (https://pubchem.ncbi.nlm.nih.gov/) and converted into PDB format through OpenBabel3.1.1 [12]. A grid box with dimension of 126 × 126 × 126 Å3 and centre x = 97.487, y = 148.695 and z = −34,111, was set for molecular docking using AutoDock Tools (ADT, version 4.2.6) [13,14], and PyMOL software (https://pymol.org) was applied for and visualization.…”
Section: Molecular Dockingmentioning
confidence: 99%
See 1 more Smart Citation
“…The impacts of compounds 14 and 15 are similar to that of C-5 (21%). 22 The discrepancy between the influence of compounds 12 and 13 in Th-T and light-scattering signals suggests that the aggregates formed in the presence of these molecules exhibit a higher affinity for Th-T, likely being richer in intermolecular βsheet.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Accordingly, we focused our attention to identify of newer αsyn aggregation inhibitors oriented toward the NAC domain of α-syn. 22 From a set of 4-amino-5−(4-pyridinyl)-4H-1,2,4triazole-derived compounds, we identified the 3-(cinnamylsulfanyl)-5-(4-pyridinyl)-1,2,4-triazol-4-amine (11) that proved to reduce α-syn aggregation in an in vitro assay. Docking studies suggested the binding into a specific site placed between N-…”
Section: ■ Introductionmentioning
confidence: 99%